PENGARUH MODIFIKASI SERVQUAL TERHADAP KEPUASAN MAHASISWA PADA AKADEMI KEBIDANAN SALMA SIAK - Imran, Imran (Ensiklopedia of Journal, 2024)
This research aims to analyze the effect of service quality (servqual) modification on students satisfaction at the Salma’s midwifery academy at Siak regency. The number of research samples are all students, 43 by census method. Then, datas collecting through questionnaires direct spreading by using a Likert scale. Analytical datas method in this research using two stages regression through reliable statistical measured by SPSS version 22 software. Research result shows that independent variables, service quality which consist of tangibles, realibility, Responsiveness, Assurance, Empathy, and technical having significant influence and positive towards student’s satisfaction, this research result is expected to intensify student preference to study at Salma’s midwifery academy.Keywords: Service Quality, Student’s Satisfactory.